Measuring Publication Efficiency in Humanities Journals: An AI-Based Analysis of Diamond Open Access Models and SINTA Rankings - Saputra, Andi; Nelisa, Malta; Nabila, Jeihan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study examines the influence of open access models, particularly Diamond Open Access (OA), and SINTA rankings on the submission-to-publication duration of accredited humanities journals in Indonesia. It also addresses a notable gap in existing literature regarding publication waiting times within the Indonesian humanities context. Employing a quantitative ex post facto design, the study analyzes a sample of 100 SINTA-accredited humanities journals that published articles in 2024. Submission-to-publication durations (calculated as the number of days between submission and final publication) were extracted using an AI-assisted metadata retrieval tool (Gemini). A total of 2,489 eligible articles were identified. Data were analyzed using descriptive statistics and one-way ANOVA to determine the effects of the independent variables. The findings show that the median submission-to-publication time for Indonesian humanities journals is 125.67 days, with substantial variability ranging from 0 to 991 days. The Diamond OA model does not significantly affect publication duration (Sig. > 0.05), indicating that author-fee-free access does not inherently lengthen editorial processes. Conversely, SINTA rankings show a significant effect (Sig. < 0.05), with journals in higher SINTA tiers tending to have longer publication timelines. This study provides timely empirical evidence regarding factors that shape publication efficiency in Indonesia’s humanities journals—an area previously underexplored. The methodological use of AI for metadata extraction also represents an important contribution. These findings offer practical insights for authors selecting suitable publication venues and for journal publishers seeking to enhance the efficiency of their editorial workflows.